2002
DOI: 10.1063/1.1491599
|View full text |Cite
|
Sign up to set email alerts
|

Directly coupled superconducting quantum interference device magnetometer fabricated in magnesium diboride by focused ion beam

Abstract: We report the fabrication of a directly coupled superconducting quantum interference device (SQUID) magnetometer in MgB 2 using a focused ion beam (FIB) to create Josephson junctions in a 70 nm thick film of MgB 2 . The SQUID shows a voltage modulation (∆V) of 175 µV at a temperature of 10 K and operates over a temperature range from 10 K to 24 K. We find excellent agreement between the measured maximum transfer functions and those predicted by theory. We have measured the magnetic flux noise at 20 K to be as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The process in this case relies on the presence of a layer of suppressed superconductivity at the base of the trench cut by the FIB; however it is unclear whether this is directly induced by Ga-ion damage or was intrinsic to the films used in the experiments. Despite the variable quality of early MgB 2 films we were able to demonstrate good SQUID performance using FIB planar Josephson junctions [19]. A variant of the process has also been used to fabricate junctions in YBa 2 Cu 3 O 7−δ via ion irradiation through focused ion beam cuts in a Au mask [13].…”
Section: Planar Sns Junction Fabrication and Characterisationmentioning
confidence: 99%
“…The process in this case relies on the presence of a layer of suppressed superconductivity at the base of the trench cut by the FIB; however it is unclear whether this is directly induced by Ga-ion damage or was intrinsic to the films used in the experiments. Despite the variable quality of early MgB 2 films we were able to demonstrate good SQUID performance using FIB planar Josephson junctions [19]. A variant of the process has also been used to fabricate junctions in YBa 2 Cu 3 O 7−δ via ion irradiation through focused ion beam cuts in a Au mask [13].…”
Section: Planar Sns Junction Fabrication and Characterisationmentioning
confidence: 99%
“…Burnell et al demonstrated that the voltage-flux characteristics of dc SQUIDs consisting of VTB junctions can be clearly observed when the trench depth in the microbridge is 70-80% of the film thickness [11], [12]. The VTB weak link was constructed by etching a 50 nm-wide track on a 4 -wide film line using a focused ion beam (FIB).…”
Section: Introductionmentioning
confidence: 99%
“…For several application purposes, thin films are required. One such application is Josephson junctions [10][11][12] which have potential use in various applications, such as superconducting quantum interference device (SQUID) [13,14], single flux quantum (SFQ) circuit. To date several methods have been reported mainly hybrid physical chemical vapour deposition (HPCVD) [15][16][17], pulsed laser deposition (PLD) [18,19], electron beam evaporation [20], molecular beam epitaxy [21][22][23], ion beam [24] and sputtering [25,26] for deposition of MgB 2 thin films.…”
Section: Introductionmentioning
confidence: 99%